The effect of foliar spraying of silver and iron nanoparticles as fertilizers on the quantity, quality, and antimicrobial properties of Melissa officinalis L. essential oil - Faezeh Nabizadeh Samani; Mansureh Ghavam; Ali Tavili; Rouhollah Mirzaei (PLoS ONE, 2025)
Melissa officinalis L. as a medicinal plant used in traditional medicine to treat headaches caused by stress, anemia, nausea, dizziness, indigestion, colic, epilepsy, hysteria, cancer, and heart failure. The present study aimed to evaluate the effect of foliar spraying of silver and iron nanoparticles as fertilizers on yield, type, chemical compounds, and antimicrobial properties of M. officinalis leaf essential oil. For this purpose, plant cultivation was conducted in May 2020 as a completely random design. After one year of establishment, foliar spraying was conducted at the beginning of flowering, the peak of flowering, and the end of flowering at the levels of 20, 40, 60, 80, and 100 mg/L, and the control of iron and silver nanoparticles. After collecting and drying the leaves, the essential oil was extracted by water distillation, and the compounds were identified by Gas chromatography–mass spectrometry. The antibacterial activity of essential oils was evaluated by using agar diffusion method, Minimum growth inhibitory concentration, and Minimum concentration of bacterial lethality. The results showed that foliar spraying with different nano iron and silver treatments had a significant effect on the yield, percentage of compounds, and antimicrobial activity of M. officinalis leaf essential oil (p ≤ 0.01). The 60 mg/L of FeNPs concentration with 1.70% (w/w) had the highest yield of M. officinalis leaf essential oil. The neral (33.5–0%), citral (28.53–0%), geranial (28.25–0%), caryophyllene (20.71–0%), caryophyllene-oxide (19.73–7.36%), and geranial acetate (5.99–11.84%) were the dominant compounds of essential oil. The results of antimicrobial test showed that the lowest MIC value belongs to the treatments of nano iron 100, nano silver 20, and nano silver 60 mg/L with a value of <62.5 μg/mL. against Pseudomonas aeruginosa, that it was one times weaker than rifampin and three times more potent than the control treatment. However, the best treatment in terms of of the essential oil efficiency was for the samples sprayed with nanoiron 60 mg/L. In terms of the essential oil componds, was for the nanoiron treatment 100 mg/L with the predominance of caryophyllene oxide and geranyl acetate, and in terms of the antimicrobial activity, was for the nano silver treatment, 60 mg/L. Therefore, they can be promising and potential natural options for the production of M. officinalis essential oil under foliar spraying with economical and environmentally friendly fertilizers for consumption in various pharmaceutical and cosmetic industries.